GE_GERICHTE P/10961/2017 vom 15. September 2020 - GE Cour de justice (2020)
IN DUBIO PRO REO;ADMINISTRATION DES PREUVES;LÉSION CORPORELLE SIMPLE;MENACE(DROIT PÉNAL);PARTIE CIVILE;TORT MORAL;INDEMNITÉ(EN GÉNÉRAL) | CP.123.al1; CPP.389.al1; CPP.139.al2; CO.47; CP.180.al1; CPP.122.al1; CPP.426.al1; CPP.428.al1; CPP.433.al1; CPP.135.al1